Localized foundering of Indian lower crust in the India–Tibet collision zone - Shi, Danian (Proc Natl Acad Sci U S A, 2020)
The deep structure of the continental collision between India and Asia and whether India’s lower crust is underplated beneath Tibet or subducted into the mantle remain controversial. It is also unknown whether the active normal faults that facilitate orogen-parallel extension of Tibetan upper crust continue into the lower crust and upper mantle. Our receiver-function images collected parallel to the India–Tibet collision zone show the 20-km-thick Indian lower crust that underplates Tibet at 88.5–92°E beneath the Yarlung-Zangbo suture is essentially absent in the vicinity of the Cona-Sangri and Pumqu-Xainza grabens, demonstrating a clear link between upper-crustal and lower-crustal thinning. Satellite gravity data that covary with the thickness of Indian lower crust are consistent with the lower crust being only ∼30% eclogitized so gravitationally stable. Deep earthquakes coincide with Moho offsets and with lateral thinning of the Indian lower crust near the bottom of the partially eclogitized Indian lower crust, suggesting the Indian lower crust is locally foundering or stoping into the mantle. Loss of Indian lower crust by these means implies gravitational instability that can result from localized rapid eclogitization enabled by dehydration reactions in weakly hydrous mafic granulites or by volatile-rich asthenospheric upwelling directly beneath the two grabens. We propose that two competing processes, plateau formation by underplating and continental loss by foundering or stoping, are simultaneously operating beneath the collision zone.